Neural Oscillation Profiles of a Premise Monotonicity Effect During Semantic Category-Based Induction - Sun, Mingze; Xiao, Feng; Long, Changquan (Frontiers in Human Neuroscience, 2019)
A premise monotonicity effect during category-based induction is a robust effect, in which participants are more likely to generalize properties shared by many instances than those shared by few instances. Previous studies have revealed the event-related potentials (ERPs) elicited by this effect. However, the neural oscillations in the brain underlying this effect are not well known, and such oscillations can convey task-related cognitive processing information which is lost in traditional ERP analysis. In the present study, the phase-locked and non-phase locked power of neural oscillations related to this effect were measured, by manipulating the premise sample size (single [S] vs. two [T]) in a semantic category-based induction task. For phase-locked power, the results illustrated that the premise monotonicity effect was revealed by anterior delta power, suggesting differences in working memory updating. The results also illustrated that T arguments evoked larger posterior theta-alpha power than S arguments, suggesting that T arguments led to enhanced subjectively perceived inductive confidence than S arguments. For non-phase-locked power, the results illustrated that the premise monotonicity effect was indicated by anterior theta power, suggesting that the differences in sample size were related to a change in the need for cognitive control and the implanting of adaptive cognitive control. Moreover, the results illustrated that the premise monotonicity effect was revealed by alpha-beta power, which suggested the unification of sentence and inference-driven information. Therefore, the neural oscillation profiles of the premise monotonicity effect during semantic category-based induction were elucidated, and support the connectionist models of category-based induction.